Performance evaluation for speaker recognition system based on cross match technique - 424899 Mohd. Alwi Abdul Aziz (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004